PENDIDIKAN LINGKUNGAN HIDUP DI DESA CIBUNIAN - Abdul Goni, Muhamad; Tohir Safy, Ahmad Sahid; Nursyifakan, Fazal; Oktapiani, Zahradita (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
The lack of public awareness of the surrounding environment is a problem that It is still ongoing today, due to lack of knowledge and infrastructure support in protecting the environment, so that concern for the environment itself very minimal. One of the causes of the lack of public concern for the environment which until now is still being done is throwing garbage out of place, So that this kind of thing many parties are harmed by each other. This kind of problem is not individual responsibility, but rather collective responsibility that involves many The party without exception of this nation. Every human action is based on ethics and morals, Without exception in treating the environment. Because this problem will continue If public awareness of caring for the environment is still minimal. Here can be found Some understanding of the environment as an effort to increase the nature of caring for milieu.